2009
DOI: 10.1108/17561390910999506
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship and marketing: an exploratory study in Mauritius

Abstract: PurposeThe purpose of this paper is to explore the importance that successful entrepreneurs in Mauritius attach to marketing in operating their business and how marketing is actually practised or is prevalent in their enterprises.Design/methodology/approachThis paper forms part of a broader study undertaken by the authors. The survey instrument is a personally administered semi‐structured questionnaire. A sample of 30 successful entrepreneurs for this paper is drawn judgmentally from the broader study.Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…That scholarly appreciation of the interconnectedness between marketing and the process of entrepreneurship has utility is further reinforced by studies which show that marketing activities have long been recognized and practiced by real life entrepreneurs (Gungaphul and Boolaky, 2009;Lam, 2004). For example, Gilmore et al's (2006) longitudinal study found that marketing was indeed an integral part of the business owners' business activities.…”
Section: Introductionmentioning
confidence: 99%
“…That scholarly appreciation of the interconnectedness between marketing and the process of entrepreneurship has utility is further reinforced by studies which show that marketing activities have long been recognized and practiced by real life entrepreneurs (Gungaphul and Boolaky, 2009;Lam, 2004). For example, Gilmore et al's (2006) longitudinal study found that marketing was indeed an integral part of the business owners' business activities.…”
Section: Introductionmentioning
confidence: 99%
“…(Baldacchino, 2005b) Island Branding, romancing the brand (Baldacchino, 2000(Baldacchino, , 2002(Baldacchino, , 2005b Maneuvering as Glocal (global but local) Citizens, Professional but Loyal Workforce (Baldacchino, 2005a) Knowledge Based Service (Baldacchino, 1998) Government Support (A.B., 1995) (Baldacchino, 2005b) (Sambajee & Dhomun, 2015) small-island "myth" brand, to emphasis their uniqueness (Scott et al, 2005) Management expertise, Marketing ability, Clear goal and objectives Set more specific and more difficult goal (T. Singh et al, 2007;van Gelder et al, 2007) human capital (education, development of skills) (van Gelder et al, 2007) strong links with customer markets, secure and activate network relationships, (Scott et al, 2005) authenticity and uniqueness (Baldacchino, 2010) Financial Capabilities, access to financing (A.B., 1995;Naidu & Chand, 2012) utilization of tourism traffic, Tourism industry as export outlet, marketing locality (tourist market and diaspora) (Baldacchino, 1998(Baldacchino, , 2000(Baldacchino, , 2002 "just in time"inventory (Baldacchino, 2002) bootstrapping strategies (Sambajee & Dhomun, 2015) Product offering based on customer needs and wants, talking and listening to the customers, maintaining close relationship with the customers. (Gungaphul & Boolaky, 2009) use local raw material, Totally natural, By-product utilization, secret recipe (Baldacchino, 2000) ICT capabilities (Baldacchino, 2005a;Scott et al, 2005) Manufacturing experience to the customer (Baldacchino, 2010) selling products via the internet…”
Section: Resultsmentioning
confidence: 99%
“…Market development context has been found in the research of Gungaphul and Boolaky [149] which has done in Mauritius island, they found that the function of marketing is significant to Mauritius entrepreneurs for their business achievement, whereas the scope of marketing is considered as a crucial driver to the success for US innovative start-ups [102].…”
Section: Market Developmentmentioning
confidence: 99%